Jack Johnson, Rebel Sojourner : Boxing in the Shadow of the Global Color Line - Runstedtler, Theresa (American crossroads, 2012)
In his day, Jack Johnson--born in Texas, the son of former slaves--was the most famous black man on the planet. As the first African American World Heavyweight Champion (1908-1915), he publicly challenged white supremacy at home and abroad, enjoying the same audacious lifestyle of conspicuous consumption, masculine bravado, and interracial love wherever he traveled. Jack Johnson, Rebel Sojourner provides the first in-depth exploration of Johnson's battles against the color line in places as far-flung as Sydney, London, Cape Town, Paris, Havana, and Mexico City. In relating this dramatic story, T.